PENURUNAN KADAR ASAM URAT DENGAN PEMBERIAN AIR REBUSAN DAUN SALAM PADA LANSIA DI DUSUN SUMBER SARI DESA TORGANDAKECAMATAN TORGAMBA KAB. LABUHAN BATU SELATAN - Husna Sari; Erlina Hayati; Dede Irma Suryani (JURNAL ILMIAH DHDT - KEBIDANAN, 2021)
Uric acid is a compound derived from purines or the end result of the breakdown of purines. Gout is an inflammatory joint disease that can cause burning, swelling, pain, and stiffness in the joints. Factors that can trigger gout are heredity (genetic), gender, age, obesity. The process of elderly people is also often experienced with decreased quality of life, so that the elderly will experience health problems such as hypertension, diabetes mellitus, gout, and stroke. Bay leaves have flavonoid compounds that are useful and beneficial for health. Bay leaves can be used as herbal medicines that can treat disease problems such as gout, diabetes, and stomach ulcers. This study aims to analyze the effect of giving bay leaf boiled water to reduce uric acid levels in the elderly. This type of research is experimental with a one-gruop pre-post test research design using probability sampling techniques with a sample size of 10 elderly. The population in the study was elderly 60-74 years. The research instrument was giving bay leaf boiled water with an observation sheet and measuring uric acid using GCU. The results of the Wilcoxon statistical test obtained a p value of 0.003 smaller than 0.05 (0.003 <0.05) so it can be concluded that H1 is accepted and H0 is rejected, which means that there is an effect of giving bay leaf boiled water on reducing uric acid levels in the elderly in Sumber Sari hamlet. Torgamba district, South Labuhan Batu regency. It is hoped that health workers can provide education to the elderly to reduce uric acid levels. It is hoped to keep uric acid levels normal.